Hybrid Electrical Interchange System in IoT-Based Egg-Hatching Equipment - Parenreng, Jumadi Mabe; Wahyuni , Maya Sari; Lia, Resky Amalia; Muliadi, Muliadi; Adiba, Fhatiah (Internet of Things and Artificial Intelligence Journal, 2024)
Manual egg hatching still requires time and human labor every day to regulate temperature, adjust humidity, and turn the eggs. This egg hatcher works using solar panels as an alternative energy source. This study aims to design and determine the results of the effectiveness of testing the hybrid electrical interchange system on IoT-based egg hatchers. The research method used is the R&D method. Based on the results of the research, switching energy sources is declared valid because the tools and applications are integrated. The average voltage difference in the battery in charging condition by turning on the tool is -0.01 Volts, proving that even though it is in charging condition when the tool is turned on, the voltage in the battery will still decrease. The measurement results of the average daily energy demand on the hatchery by applying a hybrid electrical interchange system is 0.142 kWh and without applying the system 0.163 kWh, proving by applying a hybrid electrical interchange system device more efficient use of PLN electricity due to assistance from PLTS. On-off automation of lights and fans can keep the temperature at an ideal state of 37°C-39°C, thus affecting the egg-hatching process. On-off automation using a relay connected to a mist maker also affects keeping humidity at 55%-65% humidity, humidity also affects the egg-hatching process, where the success rate in hatching eggs is maximized. Based on the results of tests carried out by the hybrid electrical interchange system on IoT-based egg hatchers, it can be concluded that this tool can maintain the stability of temperature and humidity automatically in egg hatchers well until the eggs hatch.